Host Factor SAMHD1 Restricts DNA Viruses in Non-Dividing Myeloid Cells - Hollenbaugh, Joseph A.; Gee, Peter; Baker, Jonathon; Daly, Michele B.; Amie, Sarah M.; Tate, Jessica; Kasai, Natsumi; Kanemura, Yuka; Kim, Dong-Hyun; Ward, Brian M.; Koyanagi, Yoshio; Kim, Baek (PLoS pathogens, 2013)
SAMHD1 is a newly identified anti-HIV host factor that has a dNTP triphosphohydrolase activity and depletes intracellular dNTP pools in non-dividing myeloid cells. Since DNA viruses utilize cellular dNTPs, we investigated whether SAMHD1 limits the replication of DNA viruses in non-dividing myeloid target cells. Indeed, two double stranded DNA viruses, vaccinia and herpes simplex virus type 1, are subject to SAMHD1 restriction in non-dividing target cells in a dNTP dependent manner. Using a thymidine kinase deficient strain of vaccinia virus, we demonstrate a greater restriction of viral replication in non-dividing cells expressing SAMHD1. Therefore, this study suggests that SAMHD1 is a potential innate anti-viral player that suppresses the replication of a wide range of DNA viruses, as well as retroviruses, which infect non-dividing myeloid cells.